Front Cover: Automated Bonding Analysis with Crystal Orbital Hamilton Populations (ChemPlusChem 11/2022). Issue 11 (8th August 2022) - George, Janine; Petretto, Guido; Naik, Aakash; Esters, Marco; Jackson, Adam J.; Nelson, Ryky; Dronskowski, Richard; Rignanese, Gian‐Marco; Hautier, Geoffroy
Abstract : The cover picture shows a workflow for automatic bonding analysis with Python tools (green python). The bonding analysis itself is performed with the program LOBSTER (red lobster). The starting point is a crystal structure, and the results are automatic assessments of the bonding situation based on Crystal Orbital Hamilton Populations (COHP) including automatic plots and text outputs. Coordination environments and charges are also assessed. More information can be found in the Research Article by J. George, G. Hautier, and co‐workers .